2021
DOI: 10.1021/acs.energyfuels.1c02620
|View full text |Cite
|
Sign up to set email alerts
|

PtNi Supported on ZIF-Derived Porous Carbon as a High-Efficiency Acidic Hydrogen Evolution Catalyst

Abstract: Hydrogen production by water cracking is an important means to solve the energy crisis and environmental problems. Low-Pt-content electrocatalysts can keep better balance between activity and cost. In this paper, we propose a simple and effective synthesis method to synthesize a bimetallic porous nitrogen-doped carbon (BMNC)-supported ultrafine Pt x Ni y alloy hydrogen evolution reaction (HER) catalyst. BMNC is derived from a Zn−Co zeolite imidazolate skeleton (ZIFS) and can be used as a highefficiency catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It is important to note that the Co 3 W 3 C diffraction peaks can also be seen in Figure 2, and their peak positions are at 39.85° and 42.4°, respectively, which correspond to the Co 3 W 3 C crystal face (422) and (511). The appearance of the Co 3 W 3 C phase proves that we have successfully doped Co elements into WC, [14] which demonstrates the feasibility of the idea of doping WC with Co, [15] Nevertheless, From the XRD pattern of Pt/WC‐3, the appearance of the Co 3 W 3 C phase was not observed. We speculate that it may be that the content of the Co 3 W 3 C phase is relatively low and its position is closer to the position of the diffraction peak of Pt, thus the diffraction peak of the Co 3 W 3 C phase was not found in the XRD pattern of Pt/WC‐3.…”
Section: Resultsmentioning
confidence: 89%
“…It is important to note that the Co 3 W 3 C diffraction peaks can also be seen in Figure 2, and their peak positions are at 39.85° and 42.4°, respectively, which correspond to the Co 3 W 3 C crystal face (422) and (511). The appearance of the Co 3 W 3 C phase proves that we have successfully doped Co elements into WC, [14] which demonstrates the feasibility of the idea of doping WC with Co, [15] Nevertheless, From the XRD pattern of Pt/WC‐3, the appearance of the Co 3 W 3 C phase was not observed. We speculate that it may be that the content of the Co 3 W 3 C phase is relatively low and its position is closer to the position of the diffraction peak of Pt, thus the diffraction peak of the Co 3 W 3 C phase was not found in the XRD pattern of Pt/WC‐3.…”
Section: Resultsmentioning
confidence: 89%
“…It is evident that the sample obtained from carbonization temperature of 900 • C exhibited the largest specific surface area among the three tested samples. This could suggest that the incomplete carbonization induced a less rough surface at 800 • C and the agglomeration of the derived carbon materials at 1000 • C are responsible for the relatively low specific surface area [20]. Evidently, the large specific surface area is beneficial to generation of active sites after the deposition of catalysts, which in turn can improve the utilization rate of the precious metal and the catalytic activity of the catalyst.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…8 More recently, Xu et al found that creating hierarchical pores and heteroatom doping in the carbon framework can further modulate the electrochemical activity of bimetallic alloy@ carbon. 23 Nonetheless, the fabrication of traditional bimetallic alloy@carbon hybrids has to resort to a complex synthetic process, template assistance, or harsh processing conditions, 24,25 which are time-consuming and not conducive to a large-scale fabrication of the desired materials. Moreover, the introduction of hierarchical pores and heteroatoms (such as N atom) in the carbon framework can further complicate the preparation of bimetallic alloy@carbon hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the NiCu@C-1 delivered a better electrocatalytic activity and stability than the pure NiCu alloy . More recently, Xu et al found that creating hierarchical pores and heteroatom doping in the carbon framework can further modulate the electrochemical activity of bimetallic alloy@carbon . Nonetheless, the fabrication of traditional bimetallic alloy@carbon hybrids has to resort to a complex synthetic process, template assistance, or harsh processing conditions, , which are time-consuming and not conducive to a large-scale fabrication of the desired materials.…”
Section: Introductionmentioning
confidence: 99%